KEDISIPLINAN DAN FASILITAS BELAJAR TERHADAP PRESTASI BELAJAR SEJARAH INDONESIA - Surachman Surachman; Maman Achdiyat (Herodotus: Jurnal Pendidikan IPS, 2019)
This study to determine effect of discipline and learning facilities on the learning achievement of Indonesian history subjects at Private High Schools in East Jakarta. The research method in this study is a survey method with correlation analysis. While data and information in the field were captured with the help of a questionnaire. Based on data analysis, it be concluded that:(1) There is a significant influence of discipline and learning facilities together on the achievement of learning subjects in Indonesian history. This is evidenced by the acquisition of Sig=0,000<0.05 and Fcount =10,051.(2) There is a significant influence of discipline on the achievement of learning history in Indonesia. This is evidenced by the acquisition of Sig=0.006<0.05 and tcount = 2.885. (3) There is a significant influence of learning facilities on the achievement of learning history. This is evidenced by the acquisition of Sig=0.033<0.05 and tcount = 2.192.